2017
DOI: 10.4103/ijo.ijo_872_16
|View full text |Cite
|
Sign up to set email alerts
|

Refractive and ocular biometric profile of children with a history of laser treatment for retinopathy of prematurity

Abstract: Purpose:Indian children belong to a diverse socioeconomic strata with retinopathy of prematurity (ROP) developing in mature, higher birth weight babies as well. The purpose of our study is to analyze the long-term status of refractive errors and its relationship with ocular biometry in children with ROP who were laser treated at a tertiary center in North India.Methods:Cross sectional study. Children (<16 years) enrolled from January 2014 to December 2014 with a history of laser treatment for ROP and examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Like other studies[11131417] ours also showed a significant number of eyes with predominantly high myopic SE and astigmatism [Table 4]. Many authors have concluded myopia to be associated with ROP laser treated than non-ROP infants and spontaneously regressed ROP cohort.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Like other studies[11131417] ours also showed a significant number of eyes with predominantly high myopic SE and astigmatism [Table 4]. Many authors have concluded myopia to be associated with ROP laser treated than non-ROP infants and spontaneously regressed ROP cohort.…”
Section: Discussionsupporting
confidence: 83%
“…The study depicted the long-term outcome in children treated for ROP with laser therapy. Comparison among the studies[11121314151617] about the patient characteristics are tabulated in Table 4. All the studies including the present study had much higher mean birth weight and mean gestational age compared to ETROP cohort [(703 g) and (25 weeks)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Kaur et al . [ 10 ] in this issue supports the lenticular nature of myopia with biometric comparisons. Agarkar et al .…”
mentioning
confidence: 59%
“…In our study hyperopia was observed in 36.4% eyes. Hyperopic rate varies significantly in different studies from 20% [26] to 86% [24], mainly depending on the follow-up duration of the study.…”
Section: Discussionmentioning
confidence: 99%